PERAN PENDIDIKAN DAN LATIHAN DALAM PENGEMBANGAN SDM BERBASIS KOMPETENSI - Tuti Andriani (Lembaga penelitian dan Pengabdian kepada Masyrakat, 2011)
The influence of science and technology in a variety of life is increasing, mainly because of the insistence of society demands both at the local level, national and global. To adjust and anticipate the effect of the necessary qualified human resources. In this regard, Indonesia's national development when even this requires the support of quality human resources to achieve the expected goals. Personnel who have been there most are still not able to complete the work at each level. Therefore to create a quality human being and the quality of society is a strategic decision that should be implemented in various sectors. Human resources management not only focused on the selection, placement, remuneration, training, transfers, promotions and various other actions, the focus is on the interests of labor organizations. Human development strategy, not only take into account the improved quality of human resources, known as human resource development strategy or human resources development. But in broad terms the development of human resources mainly include education and training, because with education and training is one of improving the competence of human resources.